2022
DOI: 10.3390/ijms23073631
|View full text |Cite
|
Sign up to set email alerts
|

Pirfenidone Sensitizes NCI-H460 Non-Small Cell Lung Cancer Cells to Paclitaxel and to a Combination of Paclitaxel with Carboplatin

Abstract: Pirfenidone, an antifibrotic drug, has antitumor potential against different types of cancers. Our work explored whether pirfenidone sensitizes non-small cell lung cancer (NSCLC) cell lines to chemotherapeutic treatments. The cytotoxic effect of paclitaxel in combination with pirfenidone against three NSCLC cell lines (A549, NCI-H322 and NCI-H460) was evaluated using the sulforhodamine B assay. The effects of this combination on cell viability (trypan blue exclusion assay), proliferation (BrdU incorporation as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 47 publications
(76 reference statements)
0
19
0
Order By: Relevance
“…IPF drugs are associated with the development of anti-tumor drugs such as nintedanib, an oral small molecule tyrosine kinase inhibitor initially developed for lung cancer and approved for the treatment of IPF. Pirfenidone has a sensitizing effect on the combination of paclitaxel and carboplatin used in clinical practice ( Branco et al, 2022 ). We believe that the identification of related anti-tumor drugs has potential significance for IPF treatment.…”
Section: Resultsmentioning
confidence: 99%
“…IPF drugs are associated with the development of anti-tumor drugs such as nintedanib, an oral small molecule tyrosine kinase inhibitor initially developed for lung cancer and approved for the treatment of IPF. Pirfenidone has a sensitizing effect on the combination of paclitaxel and carboplatin used in clinical practice ( Branco et al, 2022 ). We believe that the identification of related anti-tumor drugs has potential significance for IPF treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, novel therapeutic targets are required to provide these patients with enhanced treatment options. [ 55 ]. In this scenario, the use of dual target therapy using an αv𝛽6 integrin ligand conjugated with RTKI may assume a fundamental role.…”
Section: Discussionmentioning
confidence: 99%
“…In other tumoral contexts, some reports have been made in combining Paclitaxel with different repurposing agents, e.g., Duarte et al demonstrated that antimalarial drugs, such as Chloroquine, Artesunate and Mefloquine, could act synergistically with Paclitaxel for breast cancer therapy [ 31 , 32 ]. More recently, Branco et al demonstrate that Pirfenidone, an antifibrotic drug, sensitizes non-small cell lung cancer cells to Paclitaxel [ 71 ].…”
Section: Discussionmentioning
confidence: 99%